Respuesta :

a)

  F  = [tex]\frac{5}{9}[/tex](K - 273.15) + 32

- 32                          - 32

F - 32 = [tex]\frac{5}{9}[/tex](K - 273.15)

[tex]\frac{9}{5}[/tex](F - 32) = [tex]\frac{9}{5}[/tex][[tex]\frac{5}{9}[/tex](K - 273.15)]

[tex]\frac{9}{5}[/tex](F - 32) = K - 273.15

[tex]\frac{9}{5}F[/tex] - [tex]\frac{9(-32)}{5}[/tex] = K - 273.15

[tex]\frac{9}{5}F[/tex] - 57.6 = K - 273.15

    + 273.15       + 273.15  

[tex]\frac{9}{5}F[/tex] - 215.55 = K

b)

[tex]\frac{9}{5}(180)[/tex] - 215.55 = K

324 - 215.55 = K

108.45 = K


ACCESS MORE